Nonuniformity Correction for Variable-Integration-Time Infrared Camera - Nan Chen; Jiqing Zhang; Shengyou Zhong; Zhongshun Ji; Libin Yao (IEEE Photonics Journal, 2018)
A two-dimensional calibration technique is proposed to correct the spatial nonuniformity in infrared imaging systems adapting to different integration time and time-varying offset with one-time calibration. Differing from traditional calibration-based nonuniformity correction, this method calibrates nonuniformity with two-dimensional information from two integration time besides different irradiance, which conquers drawbacks of traditional calibration-based correction. First, it eliminates the dependence on integration time in calibration process and dramatically suppresses fixed pattern noise by a large attenuation factor. In addition, time-varying offset is real-time canceled by the subtraction of images integrated with normal and short time. Correction error of two-point correction and the proposed method are analyzed in detail. In experiments with cooled infrared camera, the proposed method provides enhanced uniformity even for seven-time variation of integration time using same correction coefficients. Both quantitative and qualitative comparisons to two-point correction demonstrate its superiority. The one-time calibration and shutterless correction scheme avoids interruption of the normal operation for real scene, extending the application range in practical engineering for infrared imaging systems with low complexity of computation and hardware.